Clinical evaluation of nebulized verapamil in out‐patients with pulmonary hypertension secondary to chronic obstructive pulmonary disease. (6th November 2022) - Fahimi, Fanak; Pourdowlat, Guitti; Behzadnia, Neda; Mostofi, Sahar Sadigh; Forough, Aida Sefidani; Parto, Omid; Esmaeili, Ayda
Abstract: Objective: Chronic obstructive pulmonary disease (COPD) is associated with many health complications, including pulmonary hypertension (PH). Although oral calcium channel blockers have shown promising results in managing COPD‐induced PH, significant systemic side effects may limit their use in this population. Administering verapamil through nebulization can be an alternative approach. We aim to assess the possible therapeutic effects of verapamil inhalation in out‐patients with pulmonary hypertension (PH) secondary to COPD. Methods: A double‐blind, randomized placebo‐controlled clinical trial was conducted. Patients with PH were randomly assigned to two groups of 15 participants. The intervention group received a short‐term single dose of 10 mg nebulized verapamil (4 ampoules of 2.5 mg/ml verapamil solutions). The control group received nebulized distilled water as a placebo in addition to their standard treatment throughout the study. Results: Systolic pulmonary artery pressure (sPAP) did not improve as a primary outcome significantly in patients receiving nebulized verapamil compared with those on placebo ( p  = 0.89). Spirometry results showed a significant improvement in FVC in the intervention group from 1.72 ± 0.63 to 1.85 ± 0.58 L ( p  = 0.00), and FEV1/FVC ratio decreased significantly after verapamil administration ( p  = 0.027). Conclusion: Verapamil did not improve any of the pulmonary artery or RV parameters in patients with COPD‐associated, but it did improve SpO2 and increase FVC, which revealed us possibility of verapamil in treating V/Q mismatch. The improved gas exchange may have been due to improvements in FVC as reflected in the improved spirometry. Higher doses of verapamil may be more efficacious and can be the subject of future trials. Abstract : Single dose nebulized verapamil inhalation showed improvement in V/Q mismatch throught increase FVC. Nebulized verapamil inhalation improved gas exchanged and increased spO2. Nebulized verapamil inhalation for out‐patients with pulmonary hypertension secondary to chronic obstructive pulmonary disease improved spirometric parameter. The FEV1/FVC ratio decreased significantly after verapamil administration due to more potent bronchodilator on small airways.